Building clouds with Windows Azure Pack : bring the benefits of Azure Pack to your cloud service and discover the secrets of enterprise class solutions /: bring the benefits of Azure Pack to your cloud service and discover the secrets of enterprise class solutions. (2016) - Malik, Amit
No abstract available